How does the use of evidence in policy narratives change during crises? A comparative study of New York City's pandemic school shutdowns - Nikolina Klatt; Sonja Blum (Review of Policy Research, 2024)
Narratives play an essential role in fast-paced policy making that occurs during crises. The COVID-19 pandemic brought numerous disruptions of normality, including school closures, which were intensely debated in narratives by many policy actors. Two shutdowns of New York City's public school system affected over 1.1 million students. This article investigates how scientific evidence was used in the narratives surrounding the school shutdowns in NYC by analyzing around 160 policy narratives with the Narrative Policy Framework. We ask whether and how the growing certainty of evidence on the new Coronavirus was reflected in the policy narratives in the second compared to the first shutdown. While there is increased use of scientific evidence in the second shutdown stage, this does not reflect an increased evidence base: The evolving use of evidence in policy narratives is mainly reflected in its strategic uses to support a certain policy solution within a blame-avoidance strategy.
Keywords: 320; COVID-19; crisis; evidence; Narrative Policy Framework; school shutdown; uncertainty